The Influence of Financial Management (Financial Literacy, Financial Planning, And Financial Behavior) on Generation Z For Long-Term Financial Well-Being In Drokilo Village, Kedungadem District, Bojonegoro Regency - Rizka Nur Hidayanti; Rizka Aprilia Dwi Susanti; Moh. Askiyanto (International Journal of Management and Business, 2026)
This study aims to determine the effect of financial management (financial literacy, financial planning, and financial behavior) on generation Z for long-term financial well-being. This study uses a quantitative approach, which focuses on hypothesis testing with statistical analysis tools and produces conclusions that can be generalized. In this study, the sample used was representative of generation Z aged 18-27 years who live in Drokilo Village, Kedungadem District, Bojonegoro Regency. The test tool used was multiple linear regression analysis technique with SPSS 26 software. Data were collected through a questionnaire that included questions about financial literacy, financial planning, and financial behavior. The results of this study indicate that financial literacy, financial planning, and financial behavior have a positive and significant effect on the long-term financial well-being of generation Z. Good financial literacy, financial planning, and financial behavior can help generation Z achieve their financial goals, prevent financial problems, and increase a sense of security and comfort.